2010
DOI: 10.3399/bjgp10x515412
|View full text |Cite
|
Sign up to set email alerts
|

Positive predictive values of ≥5% in primary care for cancer: systematic review

Abstract: When a patient consults a GP, part of the management of the individual involves an assessment of the probability of serious illness including malignancy. One way of expressing this probability is in terms of the positive predictive value (PPV): the proportion of people with the symptom, sign, or test result who develop cancer. Research on medical decision models reveals that probabilities and the valuation of outcomes are distorted by individuals, 1 and thus theories of behaviour based on cognitive assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 28 publications
4
85
0
4
Order By: Relevance
“…These results support these assumptions with similar positive predictive powers to those reported elsewhere. 15 However, this study found post-menopausal bleeding was also predictive of other cancers apart from uterine cancer including, cervix, ovary, breast, bladder, and blood cancer. Similarly, haematuria was predictive of ovarian, cervix, uterine, blood cancer in addition to renal tract cancer.…”
Section: Ethical Approvalmentioning
confidence: 87%
See 2 more Smart Citations
“…These results support these assumptions with similar positive predictive powers to those reported elsewhere. 15 However, this study found post-menopausal bleeding was also predictive of other cancers apart from uterine cancer including, cervix, ovary, breast, bladder, and blood cancer. Similarly, haematuria was predictive of ovarian, cervix, uterine, blood cancer in addition to renal tract cancer.…”
Section: Ethical Approvalmentioning
confidence: 87%
“…Red flag symptoms include symptoms which may indicate cancer 4,5,7,8,10,14,15 such as abdominal distension, abdominal pain, appetite loss, heartburn, indigestion, dysphagia, haematemesis, rectal bleeding, haematuria, haemoptysis, neck lump, weight loss, night sweats, breast lump, breast pain, nipple discharge or breast skin changes, dyspareunia, inter-menstrual bleeding, post-menopausal bleeding, and post-coital bleeding. A first occurrence of venous thrombo-embolism was also included as a red flag event as this can herald a previously undiagnosed cancer and recent NICE guidance recommends patients with venous thrombo-embolism have a cancer screen.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…For pharmacies in areas of 8 high deprivation, the mean number of alarm symptoms reported over the six month period was 20.67 (SD=22.7), for medium areas of deprivation the mean was 17.44 (SD=5.0) and, for low areas of deprivation, the mean was 17.0 (SD=13.1). Table 2 shows the mean number of alarm symptoms presented per pharmacy per tertile of deprivation alongside the KruskalWallis analysis for each alarm symptom.…”
Section: (100%)mentioning
confidence: 99%
“…8,9 Since the introduction of these guidelines, there is evidence that diagnostic delays for some cancers have reduced. 9 Despite this and given that the projected numbers of cancer diagnoses are set to increase, initiatives to promote the early detection of cancer remain a priority.…”
Section: Introductionmentioning
confidence: 99%